Artificial light at night alters activity, body mass, and corticosterone level in a tropical anuran. (30th June 2021) - Secondi, Jean; Mondy, Nathalie; Gippet, Jérôme Marcel Walter; Touzot, Morgane; Gardette, Vanessa; Guillard, Ludovic; Lengagne, Thierry
Abstract: Photoperiod is a major factor regulating biological rhythms in animals and plants. At low latitudes, annual variation in daylength is low and species are expected to strongly rely on photic cues to reset their circadian clocks. A corollary is that individuals should be strongly affected by sudden changes in the photic regime as those generated by artificial light at night (ALAN). We tested this hypothesis in an anuran in Costa Rica (10°N). Using an outdoor experimental design, we exposed adult cane toads Rhinella marina, a broadly distributed tropical anuran species to two ALAN intensities (0.04 and 5 lx). Locomotor activity was reduced at the lowest intensity, and the activity pattern shifted from crepuscular to nocturnal. Contrary to humans and mice in which ALAN favor obesity, toads from the two exposed groups did not gain mass whereas controls did. Corticosterone was reduced at the highest intensity, a possible consequence of the reduced activity of toads or the altered regulation of their circadian pattern. Thus, the behavioral and physiological disruption that we observed supports the hypothesis of the strong reliance on photic cues to regulate circadian rhythms and control homeostasis in this intertropical anuran. Furthermore, our results suggest that the negative effects of ALAN on physiology, in particular body mass regulation, may differ between vertebrate groups, thus preventing anticipated generalization before more comparative studies have been carried out. We stress the importance of considering the impact of the changing nocturnal environment in the intertropical zone which host the largest fraction of biodiversity. Abstract : Light pollution should more strongly affect animals at low latitudes because day length is stable year round. In Costa Rica, cane toads exposed to light at night in outdoor boxes moved less, failed to gain mass, and their corsticosterone levels dropped. Even in a species frequently occurring near human settlements strong behavioral and physiological disruption are observed, which suggests that particular attention should be paid to the effects of light pollution on animals in the intertropical zone.